Role of Magnetic Resonance Imaging Techniques and Protocols in Diagnosis and Staging of the Urinary Bladder Carcinoma in Comparison with Histopathological Findings - Raad owaid jassim; Haider Qasim Hamood; Hussein Hasan Nsaif (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Bladder cancer is the second most common type of cancer of the urinary system in the world, after prostate cancer. Thus, we use a combination of the best imaging technology in the diagnosis and treatment of bladder cancer, because of its accuracy in local staging and grading .Aim of The Study: To determine the accuracy and effectivity of MRI in early detection and diagnosis of bladder carcinoma by using different protocols and to Compare the sensitivity of MRI in staging of urinary bladder carcinoma with histopathological findings.Patients and Method: : A prospective case control study was conducted in an oncology teaching hospital /the complex of Baghdad medical city. This study involved 41 suspected patient (35male &6 female). The participants ranged from (31–83 years) throughout the period of from September 2020 to January 2021.Patients who were referred for examination and diagnosis due to pelvic pain and hematuria, or who had been suspected of having bladder cancer by ultrasound were included in the study and were evaluated by the MRI performed with an MRI scanner (1.5 Tesla ,Siemens).Results: : the study included 41 patients with bladder cancer, mean age was 64.8 years ranging from (31-83 years), about 31.7% was in 61 – 70 years, and about 24.4 was in 71–80 years, 85.4% were males, and 97.6% were smokers.82.9% with chronic renal disease( UTI ),56.1% with heterogeneous enhancement & 39% with homogenous enhancement ,4.9% non-enhanced. 38 patients with symptom of hematuria, the lesion location according to the its site in the bladder wall was 34.1% in the lateral wall,24.4% in the posterior wall. The stages of T-primary tumor in MRI common protocols was(Tis=12% ,Tia=10% ,T1=17% ,T2=18% ,T3=28% ,T4=15% ) .the accuracy and sensitivity for early stages (Tis,Ta,T1.&T2) in conventional MRI protocols)T1WI,T2WI) was Inconclusive in the diagnosis of bladder carcinoma accuracy ranging (44% – 57%) & sensitivity ranging (50% – 75%),while in both advance MRI modalities) DCE &DWI) had specificity for diagnosing stage bladder CA with DWI offering slightly higher sensitivity (SN) , negative predictive values (NPV ), positive predictive value (PPV) , and accuracy (SN: 100% vs. 100%, SP: 50% for DCE &100% for DWI, accuracy: 97.6% vs 100%, PPV: 97.5% vs. 100%, and NPV: 100% vs.100%).